Unstable approach in aviation: Mental model disconnects between pilots and air traffic controllers and interaction conflicts. (May 2019) - Lai, Hsueh-Yi; Chen, Chun-Hsien; Khoo, Li-Pheng; Zheng, Pai
Highlights: Different Shared mental models benefit team interaction with different ways. Mental model disconnects under task-related shared-mental model cause difficulty in integrating various working results. Mental model disconnects under team-related shared-mental model makes the team hard to intercept the potential risks at first opportunity. Conflicting disconnects cause one party compromises on team members' resource for optimizing their own performance. Abstract: Landing safety has long been a critical issue. To examine how system failures occur, the shared mental models (SMMs) between pilots and air traffic controllers (ATCOs) are studied. Meanwhile, to understand the context of various mental model disconnects, different categories of SMMs are also examined. Nine pilots and seven ATCOs are recruited to conduct the crew-based critical decision method. The SMMs of both parties are compared to identify the mental model disconnects associated with their interaction conflicts during landings. A key discovery of this research is that the mental model disconnects in task-related SMMs made it difficult to integrate various working results, which requires extra interaction to mitigate the contradiction in requirements. Furthermore, the conflicting disconnects caused by various priorities in a heterogeneous system are also identified, which requires further negotiation between the parties to achieve a mutually beneficial outcome. In team-related SMMs, mental model disconnects make different parties in a system hard to coordinate the respective requirements of members and also impede the prevention of system risks, both of which cause the continuation of risky operations. Finally, coordination of these SMMs forms a robust loop in which a system can actively detect and address the potential risks.